Effect of low-moderate intensity traditional Chinese exercises combined with acupuncture on patients with stable chronic obstructive pulmonary disease: study protocol for a randomized controlled trial - Duan, Hongxia; Bao, Yidie; Jiang, Linhong; Li, Peijun; Wang, Yingqi; He, Yuchen; Deng, Xinliao; Wu, Weibing; Zhang, Wei; Liu, Xiaodan (Frontiers in Medicine, 2025)
BackgroundTraditional Chinese exercises (TCEs), as a new technology for pulmonary rehabilitation, have been proven to be effective in patients with chronic obstructive pulmonary disease (COPD). However, further aggravation of dynamic hyperinflation manifested as exertional dyspnea during exercises may limit the partial therapeutic efficacy of TCEs on patients with COPD. Acupuncture therapy, internationally recognized as a complementary and alternative therapy, can effectively improve the degree of dyspnea, and it is expected to serve as an adjuvant therapy for exercise training in patients with COPD to fully realize the therapeutic efficacy of exercise training. Therefore, this study aims to explore the multidimensional and multi-system effects of the combination of pulmonary-based Qigong (PQ) exercise and acupuncture therapy on patients with COPD.MethodsThis protocol describes an assessor-blinded, data analyst-blinded, four-arm randomized controlled trial that aims to recruit 132 participants with stable COPD and randomly allocate them into pulmonary-based Qigong exercise group, acupuncture group, pulmonary-based Qigong exercise and acupuncture combined group, or control group at a 1:1:1:1 ratio. All participants will receive usual medical care and health education; those in the intervention groups will receive PQ exercise, acupuncture treatment, or a combination of both treatments three times per week for 8 weeks. The primary outcome will be the exercise endurance as assessed by a 6-min walk test. Secondary outcomes will include lung function, degree of dyspnea, diaphragmatic function, respiratory muscle strength, skeletal muscle structure, skeletal muscle function, psychological states, and quality of life. Exploratory outcomes will include the levels of inflammatory mediators. The frequency and severity of acute exacerbations of COPD will be recorded at baseline and 1 year after intervention.DiscussionThe findings of this study will clarify the effects of the combination of PQ exercise and acupuncture therapy on the multi-system function of patients with stable COPD to provide evidence for acupuncture as an adjuvant therapy for pulmonary rehabilitation.Clinical trial registrationhttps://www.chictr.org.cn, ChiCTR2300076255